The Musical Madhouse Les Grotesques de la musique. - Ellis, Katharine (Oxford University Press, Oxford, 2005)
RESUMEN: By Hector Berlioz. Ed. & trans. by Alastair Bruce; introduction by Hugh Macdonald. (University of Rochester Press, Rochester and Woodbridge, 2003).